The development of learning media in virtual classroom on topics of Thai performing arts - Rittibul, Pravit; Boontonglek, Manoch; Orachun, Riswan; Ngerndang, Artitaya; Boonsong, Panurat (Edelweiss Applied Science and Technology, 2024)
This research aims 1) to develop and test the effectiveness of learning media on Virtual Classroom on topics of Thai performing arts 2) to compare the pre- and post-learning achievements. 3) to study the satisfaction of students towards the learning media of Virtual Classroom on topics of Thai performing arts for Grade 10 students, Thammasat Khlong Luang Wittayakom School, thirty-six people were randomly selected. The research tools consisted of Learning Media Virtual Classroom on topics of Thai performing arts, pre-test and post-test media quality assessment form, satisfaction assessment form. Statistics used were mean standard deviation consistency Index of E1/E2 and t-score. The research findings were as follows: 1) The learning media development process for the Virtual Classroom on topics of Thai performing arts according to the ADDIE Model on Thai Traditional Performing Arts consisted of 4 types: 1. Khon (The Mask Dance) 2. Drama performances 3. Dance and dance performances 4. Native performances Teaching through learning media, Virtual Classroom on topics of Thai performing arts, efficiency was 82.31/85.56 which was higher than the criteria of 80/80. 2) The learning achievement of students after learning was higher than before which is different 3) Students' satisfaction after using the learning media Virtual Classroom on topics of Thai performing arts had the mean value of 4.56, at the highest level.